The Double-Edged Sword of Influencer Marketing: Insights from Skincare and Makeup Brands - Oh Zi Jian; Nur Batrisyia Mohd Yussri; Nur Dhia Batrisyia Rohisam; Nur Awatif Yusra; Nur Ariana Shaffrina Mohd Shahrir; Yashika Bhardwaj; Muhammad Hussain Siraj Ud Din; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
Influencer marketing has become a dominant promotional strategy in the skincare and makeup industry. Study shown that influencer marketing relies on the psychological effect of social proof, whereby individuals tend to imitate some behavior or preference in individuals with whom they can identify (Revinzky et al., 2025). c However, questions remain, does the investment truly pay off? While a viral post can boost brand visibility, attract new customers, and increase profits, influencer campaigns also carry risks, including controversies, financial losses, and potential damage to brand reputation. This study examines the effects of influencer marketing by analyzing how influencer credibility, perceived authenticity, customer trust, perceived negative and brand image. This findings highlight the double-edged nature of influencer marketing where convenience-driven engagement must be balanced with authenticity to maintain customer trust. Data were obtained from 160 respondents and examined to evaluate the proposed hypothesis